Mos2/h-bn/graphene heterostructure and plasmonic effect for self-powering photodetector: A review - Sundararaju U.; Haniff M.A.S.M.; Ker P.J.; Menon P.S. (MDPI AG, 2023)
Boron nitride; Electric power systems; Flexible electronics; Graphene; III-V semiconductors; Layered semiconductors; Light absorption; Molybdenum compounds; Photocurrents; Photons; Plasmonic nanoparticles; Plasmonics; Signal detection; Sulfur compounds; Absorption and scatterings; Comprehensive analysis; External power supplies; Fabrication and characterizations; Hexagonal boron nitride (h-BN); Material characterizations; Photocurrent generations; Research opportunities; Photodetectors